2017
DOI: 10.1155/2017/4345205
|View full text |Cite
|
Sign up to set email alerts
|

Functional Activation-Informed Structural Changes during Stroke Recovery: A Longitudinal MRI Study

Abstract: Objective Neuroimaging studies revealed the functional reorganization or the structural changes during stroke recovery. However, previous studies did not combine the functional and structural information and the results might be affected by heterogeneous lesion. This study aimed to investigate functional activation-informed structural changes during stroke recovery. Methods MRI data of twelve stroke patients were collected at four consecutive time points during the first 3 months after stroke onset. Functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, the mechanism by which the neural effects of electrical stimulation are achieved is not fully elucidated, yet few clinical trials have included neurophysiological or functional neuroimaging techniques in their protocols. Functional magnetic resonance and molecular brain imaging, such positron emission tomography and single photon emission computed tomography, have been useful in understanding the neural mechanisms after brain disease; however, they are expensive and hardly available techniques [71,72]. Exploring functional connectivity using cheaper and more portable techniques such as fNIRS will be implemented to analyse its feasibility and to further explore the mechanisms underlying the effect of tDCS in the recruited subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the mechanism by which the neural effects of electrical stimulation are achieved is not fully elucidated, yet few clinical trials have included neurophysiological or functional neuroimaging techniques in their protocols. Functional magnetic resonance and molecular brain imaging, such positron emission tomography and single photon emission computed tomography, have been useful in understanding the neural mechanisms after brain disease; however, they are expensive and hardly available techniques [71,72]. Exploring functional connectivity using cheaper and more portable techniques such as fNIRS will be implemented to analyse its feasibility and to further explore the mechanisms underlying the effect of tDCS in the recruited subjects.…”
Section: Discussionmentioning
confidence: 99%
“…New insights in the therapeutic effects of exercise after ischemic stroke are available, showing benefits in restoring brain damage as well as functional rehabilitation ( Luo et al, 2007 ; Voss et al, 2013 ; Zhang et al, 2013 ). While there is general consensus that recovery of brain connectivity (structural and functional) is crucial for functional stroke rehabilitation, studies investigating the impact of exercise on brain networks are lacking ( Wu et al, 2017 ). Therefore, we assessed the impact of voluntary exercise on the recovery of stroke induced mice with a combination of functional and structural MRI measures (DTI, rsfMRI, CBF), behavioral parameters, molecular markers (inflammation, vascular density and quality, angiogenesis) and compared their recovery to a control group without access to running wheels.…”
Section: Discussionmentioning
confidence: 99%
“…A persistent lack of knowledge exists concerning efficacy of voluntary exercise in recovering of structural and functional brain networks and subsequent functional recovery after stroke ( Wu et al, 2017 ). The cerebral capability for functional changes, such as better connectivity between brain regions, as well as structural changes, including better WM integrity, has been reported to be crucial for motor function recovery ( Wu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we can infer that the PMA plays a more crucial role in motor execution in hemiplegic patients. In addition, some studies have reported that activation during dominant hand movements is relatively greater than that during non-dominant hand movements (Wu et al, 2017). Therefore, in this study, we also compared the EEG signals between brain regions during the execution of right-handed movements in healthy participants and patients with right hemiplegia and discovered that the activation of the movement-related brain regions was greater than that of healthy participants during the execution of movements in patients with hemiplegia and that the activation of the PMA was more evident, similar to the findings of the study conducted by Chunyong et al (2023).…”
Section: Pma Plays a Significant Role In MI And Mementioning
confidence: 99%